Cover Image, Volume 16, Issue 1. (21st February 2018) - Keller, Alexandra; Wingelhofer, Bettina; Peter, Barbara; Bauer, Karin; Berger, Daniela; Gamperl, Susanne; Reifinger, Martin; Cerny‐Reiterer, Sabine; Moriggl, Richard; Willmann, Michael; Valent, Peter; Hadzijusufovic, Emir
Abstract : The cover image, by Alexandra Keller et al., is based on the Original Article The JAK2/STAT5 signaling pathway as a potential therapeutic target in canine mastocytoma, DOI:10.1111/vco.12311 Abstract : The cover image, by Alexandra Keller et al., is based on the Original Article The JAK2/STAT5 signaling pathway as a potential therapeutic target in canine mastocytoma, DOI:10.1111/vco.12311